Adenosarcoma of uterus in mother and mucinous carcinoma of breast in daughter: a rare case study - Reddy, Samskruthi S.; Nagesh, Kavya; V., Shashikala; Modugala, Vandana; Girigoudar, Arpita; Prasad, Madhva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Adenosarcoma is an infrequent malignancy which consists of benign glandular epithelium and malignant mesenchymal component. We report a 63-year-old woman diagnosed with adenosarcoma with sarcomatous overgrowth of the uterine corpus, with history of mucinous carcinoma of the breast in her daughter. Although endometrial and breast cancers share few similar hormonal, reproductive and genetic risk factors, the association of endometrial cancer with breast carcinoma is not well established. 63 years old, P4L4, postmenopausal lady presented to our hospital with post-menopausal spotting, foul smelling vaginal discharge and pain abdomen for 1 week. After evaluation she underwent total abdominal hysterectomy with bilateral salpingo-oopherectomy. Intraoperatively, a pedunculated fundal polyp measuring 6×7 cm distending the uterine cavity was noted. Post-operative histopathology examination was reported as adenosarcoma with sarcomatoid overgrowth of the uterine cavity. Immunohistochemistry revealed CK7 (epithelium (+), Vimentin (+), cluster of differentiation 10 (CD10) (+) and, Wilms tumor 1 (-). The possible association between these two conditions, adenosarcoma of uterus in mother and mucinous carcinoma of breast in daughter is explored and presented in this case report.